Code-Mixing Analysis in Speech Act Used by Classy FM Radio Announcer - Helmita Helmita (Jurnal Ilmiah Langue and Parole, 2020)
This study uses sociopragmatic theory, especially regarding code-mixing in speech acts at opening an event, greeting the listeners, and talking to interviewees. The purpose of writing is to determine the form of code-mixing and explain the meaning of the code-mixing used by the radio announcer, whether it is entered into locus, illocution, or perlocution. This paper is divided into three stages. The first stage is to provide data using the listening method by listening to radio broadcasts followed by the recording method. At the analysis stage, the data obtained were analyzed using related theories. At the last stage, it is making the conclusions and suggestions. In this research, the average Classy FM radio announcers use code-mixing in their speech acts when broadcasting. Apart from being influenced by the names of the programs that is titled in English, it is also influenced by the standardization of the words used by Classy FM itself. For example, to invite the listeners to keep listening, the term”keep in tune" is used. The term of Classy FM listeners refers to the term ”Classy People," and many other terms are used. Besides, it is also found that in one speech act, there are three types of actions that are included in it, namely the act of locus, illocution, and perlocution. Although there are also some data found only in the locus (speech acts to state something).